Hramba digitalnega gradiva v televizijskem arhivu - Lavrenčič, Aleksander (Knjižnica, 2011)
The digital world will transform archives which are now perceived as endless shelves loaded with film and tape rolls preferably located in the basement. The purpose of archiving will continue to be to preserve the material and make it available to programme makers and other users quickly and easily. The server system named "krava" is a tool which supports journalist's work with agency news. It enables quick access to information and access to audio video materials in low resolution. Therefore we decided to puh the data from the Archive's data base into server system to enable quick access to archive materials and the operation of the robotized library.
Keywords: televizijski arhivi; digitalni arhivi; arhiviranje; digitalizacija; digitization; Slovenia; Slovenija